Classification of Geriatric Low Back Pain Based on Hip Characteristics With a 12-Month Longitudinal Exploration of Clinical Outcomes: Findings From Delaware Spine Studies. Issue 12 (24th September 2021) - Hicks, Gregory E; Pohlig, Ryan T; Coyle, Peter C; Sions, J Megan; Weiner, Debra K; Pugliese, Jenifer M; Velasco, Teonette O; O'Brien, Victoria A
Abstract: Objective: The purpose of this study is to identify geriatric chronic low back pain (LBP) subgroups based on the presence of potentially modifiable hip impairments, using Latent Variable Mixture Modeling (LVMM), and to examine the prospective relationship between these subgroups and key outcomes over time. Methods: Baseline, 3-month, 6-month, and 12-month data were collected from a prospective cohort of 250 community-dwelling older adults with chronic LBP. Comprehensive hip (symptoms, strength, range of motion, and flexibility), LBP (intensity and disability), and mobility function (gait speed and 6-Minute Walk Test) examinations were performed at each timepoint. Baseline hip measures were included in LVMM; observed classes/subgroups were compared longitudinally on LBP and mobility function outcomes using mixed models. Results: Regarding LVMM, a model with 3 classes/subgroup fit best. Broadly speaking, subgroups were differentiated best by hip strength and symptom presence: subgroup 1 = strong and nonsymptomatic, subgroup 2 = weak and nonsymptomatic, and subgroup 3 = weak and symptomatic (WS). Regarding longitudinal mixed models, all subgroups improved in most outcomes over time. Specifically, over 12 months, the nonsymptomatic subgroups had lower LBP intensity and disability levels compared with the WS subgroup, whereas the strong and nonsymptomatic subgroup had better mobility function than the 2 "weak" subgroups. Conclusion: These subgroup classifications may help in tailoring specific interventions in future trials. Special attention should be given to the WS subgroup given their consistently poor LBP and mobility function outcomes. Impact: Among older adults with chronic low back pain, there are 3 hip subgroups: "strong and nonsymptomatic, " "weak and nonsymptomatic, " and "weak and symptomatic." People in these subgroups demonstrate different outcomes and require different treatment; proper identification will result in tailored interventions designed to benefit individual patients. In particular, people in the WS subgroup deserve special attention, because their outcomes are consistently poorer than those in the other subgroups.